A selection process as a game - Ferreira, Manuel Alberto M. (2018)
The aim of this paper is to exemplify how to solve the problem of selecting a candidate up to his/her acceptance trough game theory. The originality this paper proposes is how this problem will be approached: it will be treated as a single game which is made up of two parts, going as far as to state that the payoffs in the first part of the game will be the mediators of the second part of the game.